x*x+4x-3=0

Simple and best practice solution for x*x+4x-3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x*x+4x-3=0 equation:


Simplifying
x * x + 4x + -3 = 0

Multiply x * x
x2 + 4x + -3 = 0

Reorder the terms:
-3 + 4x + x2 = 0

Solving
-3 + 4x + x2 = 0

Solving for variable 'x'.

Begin completing the square.

Move the constant term to the right:

Add '3' to each side of the equation.
-3 + 4x + 3 + x2 = 0 + 3

Reorder the terms:
-3 + 3 + 4x + x2 = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 4x + x2 = 0 + 3
4x + x2 = 0 + 3

Combine like terms: 0 + 3 = 3
4x + x2 = 3

The x term is 4x.  Take half its coefficient (2).
Square it (4) and add it to both sides.

Add '4' to each side of the equation.
4x + 4 + x2 = 3 + 4

Reorder the terms:
4 + 4x + x2 = 3 + 4

Combine like terms: 3 + 4 = 7
4 + 4x + x2 = 7

Factor a perfect square on the left side:
(x + 2)(x + 2) = 7

Calculate the square root of the right side: 2.645751311

Break this problem into two subproblems by setting 
(x + 2) equal to 2.645751311 and -2.645751311.

Subproblem 1

x + 2 = 2.645751311 Simplifying x + 2 = 2.645751311 Reorder the terms: 2 + x = 2.645751311 Solving 2 + x = 2.645751311 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 2.645751311 + -2 Combine like terms: 2 + -2 = 0 0 + x = 2.645751311 + -2 x = 2.645751311 + -2 Combine like terms: 2.645751311 + -2 = 0.645751311 x = 0.645751311 Simplifying x = 0.645751311

Subproblem 2

x + 2 = -2.645751311 Simplifying x + 2 = -2.645751311 Reorder the terms: 2 + x = -2.645751311 Solving 2 + x = -2.645751311 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = -2.645751311 + -2 Combine like terms: 2 + -2 = 0 0 + x = -2.645751311 + -2 x = -2.645751311 + -2 Combine like terms: -2.645751311 + -2 = -4.645751311 x = -4.645751311 Simplifying x = -4.645751311

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.645751311, -4.645751311}

See similar equations:

| 7(2l+8)=112 | | -15x-40=5x | | x-x=100 | | y=550+40x | | -15=-3(1x+8) | | 24h+-35=853 | | 2x*2x-7x-2=0 | | 2x*2x-7-2=0 | | 5(x+3)-3x=7 | | 2x+71=9x+76 | | Xplus(-0.0025)=0.0024 | | -3x+13=10 | | -8(1x-11)=5x-68 | | 5x+7=8x-3 | | -2+5=-3 | | 2(1x+10)=-8 | | 9x+4=7-(5x-6) | | -9(1x-12)=-1x+68 | | lny=x+c | | 2(x-5)=3x+9 | | 5+35x=28x+11 | | X-3-5=7x | | 5(a-3)=95 | | 4x+16=x-35 | | x^2=8x+33 | | (u+2)*9=27 | | cosx-3sinx=0 | | 3x+7=x-16 | | 20x+16=6x-18 | | 5+78x=39x+23 | | 2x+8=-26 | | 49-2x=14-7x |

Equations solver categories